A calcium catalysed regioselective (5-exo dig) tandem process for the synthesis of fully substituted furans12. Issue 34 (21st March 2016) - Yaragorla, Srinivasarao; Dada, Ravikrishna; Pareek, Abhishek; Singh, Garima
Abstract : An efficient and highly regioselective synthesis of fully substituted furans has been described using Ca(OTf)2 . The reaction proceeds through tandem alkylation, 5- exo dig cyclisation and isomerization under solvent free conditions. Abstract : An efficient and highly regio-selective synthesis of fused & substituted furans has been described using Ca(OTf)2 as the catalyst. This tandem process involves alkylation, 5- exo dig cyclisation and isomerization to furnish densely substituted furans under solvent free conditions. A case study of regioselectivity has been demonstrated.